2017
DOI: 10.1177/0733464817716970
|View full text |Cite
|
Sign up to set email alerts
|

Coping, Cognitive Emotion Regulation, and Burnout in Long-Term Care Nursing Staff: A Preliminary Study

Abstract: Direct care workers (e.g., certified nursing assistants [CNAs]) employed in long-term care (LTC) are particularly vulnerable to the experience of burnout, yet they have received relatively less research attention compared to Licensed Practical Nurses and Registered Nurses. Within the burnout literature, evidence suggests that the deployment of certain coping strategies influences levels of burnout. The current study examined the extent to which coping (e.g., problem-focused, emotion-focused, and dysfunctional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 53 publications
7
45
2
2
Order By: Relevance
“…Professional caregiving is often very physically demanding, which can result in injury [2,3]. Such demands can increase the possibility of accidents [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional caregiving is often very physically demanding, which can result in injury [2,3]. Such demands can increase the possibility of accidents [14].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this growing demand, it is important to consider the needs of professional caregivers in order to ensure that they can provide the best care. Furthermore, the needs of professional caregivers can be framed by the physical and mental/emotional demands of their work [2][3][4][5]. Using both a quantitative and qualitative approach, the Caring for Paid Professional Caregivers Survey research study explored the health status and quality of life of LTC and AL professional caregivers (hereafter "caregivers") in the province of Alberta, Canada, as well as factors predicted to influence these health aspect and caregiver dedication to quality care [6].…”
Section: Introductionmentioning
confidence: 99%
“…And in the second place, they suffer from burnout. Positive reappraisal, one cognitive emotion regulation strategy, was significantly associated with depersonalization, and shorter sleep duration was associated with significantly greater depersonalization (Bamonti et al, 2019).…”
Section: Training Programs For Caregiversmentioning
confidence: 95%
“…A study of critical care nurses in Iran showed that ER training was effective in decreasing occupational stress . Furthermore, it was found that nurses who had difficulty coping or regulating emotions at work experienced depersonalization and emotional exhaustion after work . This negative effect seemed to be higher among nurses with fewer job resources at work .…”
Section: Uses Of the Ermentioning
confidence: 99%
“…Intrapersonal consequences, on the other hand, may have implications to the nurse's health. Some negative intrapersonal consequences include burnout, emotional exhaustion, and depersonalization (Bamonte et al, 2017).…”
Section: Antecedents and Consequencesmentioning
confidence: 99%